The Role of Organizational Support Perceived as a Moderation of the Influence of Competencies and Work Ethic on Job Satisfaction - Fina Nur Kholisah; Survival; Mulyono (Journal of Management Research and Studies, 2024)
The aim of this research is to empirically determine the role of perceived organizational support as a moderator of the influence of competence and work ethic on job satisfaction among PT employees. Amartha Micro Fintek Malang Branch. This research is positivism research, with the type of research being explanatory research. The population in this study were all employees of PT. Amartha Mikro Fintek Malang Branch, totaling 53 people. The number of samples in this study was determined based on total sampling. The data analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS application. The research results show that competence can increase job satisfaction. Work ethic can increase job satisfaction. Perceived organizational support can increase job satisfaction. Competency is able to increase job satisfaction moderated by the perceived organizational support of employees. Work ethic is able to increase job satisfaction moderated by perceived organizational support